Prevalence and pattern of hypodontia in the permanent dentition of 3374 Iranian orthodontic patients - Fariborz Amini (Dental Research Journal, 2012)
Background : Hypodontia is the most common dental anomaly and might cause clinical complications. The aim of this study was to assess the prevalence and pattern of congenital missing in the permanent dentition dentition (excluding third molars), among Iranian orthodontic patients. Materials and Methods : In this descriptive cross-sectional study, all approved panoramic radiographs of 3374 orthodontic patients (aged 10 to 20 years old), who had visited the Orthodontic Departments of all Tehran Dentistry Universities and 10 private clinics during the years 1999 to 2009 were investigated, to establish the prevalence of hypodontia in the permanent dentition (excluding third molars). The data were analyzed using a chi-square test (α = 0.01). Results : Included were 2012 female and 1362 male patients. The prevalence of hypodontia was 5.21% (5.86% in females, 4.25% in males). The difference between the genders in terms of missing teeth was not significant (P = 0.202). A total of 298 teeth were missing (166 in females, 132 in males). The average of missing per individual was found to be 1.69 (1.40 missing for each girl, 2.32 for each boy). There was no significant difference between the number of missing teeth in males and females (P = 0.160). The most common missing teeth were maxillary lateral incisors (37.2%), mandibular second premolars (22.1%), and mandibular central incisors (10.7%). In both unilateral and bilateral hypodontia cases, the maxillary lateral had the highest prevalence of missing, followed by the mandibular second premolar. Missing was significantly more frequent (P = 0.001) in the maxilla (5.3%) compared to the mandible (3.5%). Conclusion : Out of every 20 Iranian orthodontic patients, one might have some missing permanent teeth, needing early attention. Hypodontia was more prevalent in females (though not significantly) and in the maxilla. Although more females were affected, the number of missing per individual was greater in males.